A study of difficulties in algebra among college students at the Philippine Normal College, 1973-1974 - Cruz, Francis Reyes ([Quezon City s.n], 1974)
This study identified the difficulties encountered by the students of the Philippine Normal College in some major areas of College Algebra during the second semester school year 1973-1974. It was revealed that the students encountered difficulties in the following areas of Algebra (from the most difficult to the least): graphing linear equations, solving linear and quadratic equations, using the laws of exponents, simplification, finding special products and factoring, performing fundamental operations and problem solving.
Thesis (M.A.T.)--University of the Philippines.
Keywords: Algebra